Comparative winter nutrition of elk in the Jemez Mountains, New Mexico - Rowland, Mary M., author; Alldredge, A. William, advisor; White, Gary C., committee member; Bailey, J. A., committee member (Colorado State University. Libraries, 1981)
Diet quality and nutritional status of elk {Cervus elaphus nelsoni) were studied in the Jemez Mountains, New Mexico, during January-April 1980. A recently burned montane area, including portions of Bandelier National Monument, and an unburned upper montane area in the Valle San Antonio were selected for winter range comparisons. Botanical composition of elk diets, determined by microhistological analysis of feces, was markedly different between the 2 areas, passes dominated diets in the burned area (x =90%), but were consumed in nearly equal proportions with browse in the unburned area (x = 52%, grasses; x = 41%, browse). Forbs were minor dietary components in both areas. Diet botanical com-position did not vary during the winter and early spring. Grasses were more digestible than was browse, but crude protein content was similar between forage classes. Temporal increases in quality of grasses were significant, whereas browse forages remained relatively constant in quality. Comparisons of forage protein and IVDOM (in vitro digestible organic matter) revealed no differences between locations. Dietary protein ranged from 3.5-7.2% in Bandelier and from 4.7-7.5% in the Valle San Antonio, and was consistently superior in the unburned area. Increases in diet IVDOM in Bandelier (35% to 48%) surpassed those in the Valle San Antonio (33% to 39%) and were more rapid in Bandelier. Increases in diet quality were highly correlated with changes in quality of grasses consumed by elk. Observed disparities in diet quality between areas were caused primarily by differences in diet compositions and the differing qualities of grasses vs. browse. Forage quality was more variable than was diet quality, indicating the ability of elk to maintain relatively constant diet quality when confronted with large fluctuations in forage quality. A simulation model of ruminant energy and nitrogen balance was used to predict potential effects of diet quality on elk nutritional status. Greater energy deficits were predicted for elk in the unburned area, effecting greater losses of fat and lean body. Superior dietary nitrogen in the unburned area was insufficient to compensate for these losses.
Keywords: Elk -- Feeding and feeds; Elk -- New Mexico